The epidermal growth factor receptor is involved in angiotensin II but not aldosterone/salt-induced cardiac remodelling. - Smail Messaoudi (Public Library of Science (PLoS), 2012)
Experimental and clinical studies have shown that aldosterone/mineralocorticoid receptor (MR) activation has deleterious effects in the cardiovascular system; however, the signalling pathways involved in the pathophysiological effects of aldosterone/MR in vivo are not fully understood. Several in vitro studies suggest that Epidermal Growth Factor Receptor (EGFR) plays a role in the cardiovascular effects of aldosterone. This hypothesis remains to be demonstrated in vivo. To investigate this question, we analyzed the molecular and functional consequences of aldosterone exposure in a transgenic mouse model with constitutive cardiomyocyte-specific overexpression of a mutant EGFR acting as a dominant negative protein (DN-EGFR). As previously reported, Angiotensin II-mediated cardiac remodelling was prevented in DN-EGFR mice. However, when chronic MR activation was induced by aldosterone-salt-uninephrectomy, cardiac hypertrophy was similar between control littermates and DN-EGFR. In the same way, mRNA expression of markers of cardiac remodelling such as ANF, BNF or β-Myosin Heavy Chain as well as Collagen 1a and 3a was similarly induced in DN-EGFR mice and their CT littermates. Our findings confirm the role of EGFR in AngII mediated cardiac hypertrophy, and highlight that EGFR is not involved in vivo in the damaging effects of aldosterone on cardiac function and remodelling.